Biodegradation of secondary microplastics by selected bacterial consortium in mangrove sediments under laboratory conditions / Mehran Sanam Bhatti - Mehran Sanam , Bhatti (2019)
Universal abundance of microplastics poses a grave threat to the welfare of human beings and other living organisms. Hence, biodegradation is often suggested for remediation of microplastic pollution in the environment. Thus, the objectives of this research were to investigate the effect of daily input of bacterial inoculum on biodegradation, to study the effect of different concentrations of inoculum on biodegradation, and to explore the effect of different size of microplastics on their biodegradation. Research experiments were carried out in homogenized mangrove soil that was collected from 0 – 5 cm depth from six mangrove sites in Peninsular Malaysia. Three types of microplastic namely, High-Density Polyethylene (HDPE), Polypropylene (PP) and Polystyrene (PS) were chosen to study the impact of daily application of inoculum, while PP and PS were selected to further investigate the effect of concentration of inoculum and microplastic size due to their higher resistance to biodegradation. A consortium of nine bacteria was used as inoculum. Three methods were selected to determine biodegradation of microplastics namely weight loss, Fourier-transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM). When microplastics were treated with inoculum on daily basis, 1.26% of weight loss was observed for HDPE, 1.15% for PP, and 0.5% for PS. Whereas, the lowest concentration of inoculum resulted in higher degradation of PS as weight loss recorded was 0.17%. Lastly, 1–4 mm2 PP showed the most weight reduction of 0.5%. No significant differences between weight loss values of treated and control microplastics was found except for PP treated 1% inoculum concentration. Despite the low weight loss values, FTIR spectra of treated microplastics have shown evidence of biodegradation with the changes in peak intensities and absence of typical peaks. The formation of new peaks indicated disappearance of typical functional groups and appearance of new functional groups due to polymer oxidation. Similarly, SEM analysis of treated PP and PS of 1-4 mm2 with 0.25% inoculum concentration, showed formation of pits and surface erosion suggesting structural damages to microplastics due to assimilation of polymers by microbes. Selected bacterial consortium has shown the capabilities of biodegradation of HDPE, PP and PS. The rate constant of microplastics treated with daily application of inoculum suggested higher rate of biodegradation for HDPE, PP and PS which was 0.002 day-1, 0.00018 day-1 and 0.00008 day-1, respectively. Similarly, among other sizes of microplastics, 1-4 mm2 sized PP and 25 mm2 sized PS have shown higher biodegradation rate of 0.000056 day-1 and 0.000011 day-1, respectively as well.